Tuberculosis ileocecal en el niño: Pseudotumoral form - Arruti, César; Torres, Daniel H.; Scarrone, Héctor; Falconi, Luis (Cirugía del Uruguay, 1979)
The author describes a rare case in infantile surgery of intestinal tuberculosis during the course of pulmonary disease. The paper contains a review of clinical and radiologic symptomatology and of corresponding therapy. Evolution was favourable.